Dynamic Circuit Specialisation for Key-Based Encryption Algorithms and DNA Alignment - Tom Davidson; Fatma Abouelella; Karel Bruneel; Dirk Stroobandt (International Journal of Reconfigurable Computing)
Parameterised reconfiguration is a method for dynamic circuit specialization on FPGAs. The main advantage of this new concept is the high resource efficiency. Additionally, there is an automated tool flow, TMAP, that converts a hardware design into a more resource-efficient run-time reconfigurable design without a large design effort. We will start by explaining the core principles behind the dynamic circuit specialization technique. Next, we show the possible gains in encryption applications using an AES encoder. Our AES design shows a 20.6% area gain compared to an unoptimized hardware implementation and a 5.3% gain compared to a manually optimized third-party hardware implementation. We also used TMAP on a Triple-DES and an RC6 implementation, where we achieve a 27.8% and a 72.7% LUT-area gain. In addition, we discuss a run-time reconfigurable DNA aligner. We focus on the optimizations to the dynamic specialization overhead. Our final design is up to 2.80-times more efficient on cheaper FPGAs than the original DNA aligner when at least one DNA sequence is longer than 758 characters. Most sequences in DNA alignment are of the order 213.